Biomolecular Perturbations in In-Cell Dynamic Nuclear Polarization Experiments - Overall, Sarah A.; Barnes, Alexander B. (Frontiers in Molecular Biosciences, 2021)
In-cell DNP is a growing application of NMR to the study of biomolecular structure and function within intact cells. An important unresolved question for in-cell DNP spectroscopy is the integrity of cellular samples under the cryogenic conditions of DNP. Despite the rich literature around cryopreservation of cells in the fields of stem cell/embryonic cell therapeutics, cell line preservation and in cryo-EM applications, the effect of cryopreservation procedures on DNP parameters is unclear. In this report we investigate cell survival and apoptosis in the presence of cryopreserving agents and DNP radicals. We also assess the effects of these reagents on cellular enhancements. We show that the DNP radical AMUPol has no effect on membrane permeability and does not induce apoptosis. Furthermore, the standard aqueous glass forming reagent, comprised of 60/30/10 d8-glycerol/D2O/H2O (DNP juice), rapidly dehydrates cells and induces apoptosis prior to freezing, reducing structural integrity of the sample prior to DNP analysis. Preservation with d6-DMSO at 10% v/v provided similar DNP enhancements per unit time compared to glycerol preservation with superior maintenance of cell size and membrane integrity prior to freezing. DMSO preservation also greatly enhanced post-thaw survival of cells slow-frozen at 1 oC/min. We therefore demonstrate that in-cell DNP-NMR studies should be done with d6-DMSO as cryoprotectant and raise important considerations for the progression of in-cell DNP-NMR towards the goal of high quality structural studies.